2014
DOI: 10.1016/j.dental.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Properties of axially loaded implant–abutment assemblies using digital holographic interferometry analysis

Abstract: This study gained in vitro implant performance data, compared the deformations in implant bodies and numerically stated the biomechanical benefits of wider diameter implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the elastic modulus of enamel is 40-80 GPa, while it is around 30 GPa in peritubular dentin and 16-21 GPa in inter-tubular dentin. It may be even lower (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) GPa) in regions as close as 500 μm from the pulp [28,29]. Chan et al found that enamel had an elastic modulus of ∼95 GPa, whereas dentin had an elastic modulus of ∼19 GPa from nano-indentation tests [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the elastic modulus of enamel is 40-80 GPa, while it is around 30 GPa in peritubular dentin and 16-21 GPa in inter-tubular dentin. It may be even lower (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) GPa) in regions as close as 500 μm from the pulp [28,29]. Chan et al found that enamel had an elastic modulus of ∼95 GPa, whereas dentin had an elastic modulus of ∼19 GPa from nano-indentation tests [30].…”
Section: Discussionmentioning
confidence: 99%
“…Digital moiré interferometry (DMI) was applied to decipher the dentin tissue biomechanics by fabricating gratings with ultra-high quality on an extremely flat surface [7]. Brozović J used digital holographic interferometry (DHI) to determine the properties of axially loaded dental implant-abutment assemblies [8]. Asundi and Kishen utilized photoelasticity to evaluate stress distribution, from the root surface to the supporting bone under clinical conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Photomechanical experiments such as photoelasticity , electronic speckle interferometry (ESPI) , digital holographic interferometry (DHI) , digital moiré interferometry (DMI) , optical coherence tomography (OCT) and digital image correlation (DIC) have been employed to study biomechanical responses of dental structures. However, very few techniques have determined 3D deformation states (eg, displacements, principle strains) on dentin structure in real‐time, under a fully hydrated condition to a nonhydrated state.…”
Section: Introductionmentioning
confidence: 99%